2017
DOI: 10.1212/wnl.0000000000004396
|View full text |Cite
|
Sign up to set email alerts
|

Human dorsal root ganglion in vivo morphometry and perfusion in Fabry painful neuropathy

Abstract: Patients with Fabry disease have severely enlarged dorsal root ganglia with dysfunctional perfusion. This may be due to glycolipid accumulation in the dorsal root ganglia mediating direct neurotoxic effects and decreased neuronal blood supply. These alterations were less pronounced in peripheral nerve segments. Thus, the dorsal root ganglion might play a key pathophysiologic role in the development of neuropathy and pain in Fabry disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 42 publications
2
65
0
1
Order By: Relevance
“…In line with this, FD patients show reduced intra‐epidermal nerve fiber density and impaired thermal perception . Several lines of evidence indicate that the origin of the peripheral pain presumably lies in the accumulation of Gb3 within peripheral nerves and/or dorsal root ganglion (DRG) that might lead to degeneration of small sensory fibers . In this regard, it has been recently demonstrated that the α‐Gal A (−/0) hemizygous male mice (FD mouse model), which share many symptoms with FD patients, present molecular and structural changes in peripheral nerves which underlie pain and sensory‐perceptual alterations such as heat/cold hyperalgesia and mechano‐hyperalgesia …”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In line with this, FD patients show reduced intra‐epidermal nerve fiber density and impaired thermal perception . Several lines of evidence indicate that the origin of the peripheral pain presumably lies in the accumulation of Gb3 within peripheral nerves and/or dorsal root ganglion (DRG) that might lead to degeneration of small sensory fibers . In this regard, it has been recently demonstrated that the α‐Gal A (−/0) hemizygous male mice (FD mouse model), which share many symptoms with FD patients, present molecular and structural changes in peripheral nerves which underlie pain and sensory‐perceptual alterations such as heat/cold hyperalgesia and mechano‐hyperalgesia …”
Section: Introductionmentioning
confidence: 82%
“…[9][10][11] Several lines of evidence indicate that the origin of the peripheral pain presumably lies in the accumulation of Gb3 within peripheral nerves and/or dorsal root ganglion (DRG) that might lead to degeneration of small sensory fibers. 3,12 In this regard, it has been recently demonstrated that the α-Gal A (−/0) hemizygous male mice (FD mouse model), which share many symptoms with FD patients, present molecular and structural changes in peripheral nerves which underlie pain and sensory-perceptual alterations such as heat/cold hyperalgesia and mechano-hyperalgesia. [13][14][15][16][17] Functional GI disorders (FGIDs) are complex multisystem pathologies that involve abnormalities in GI secretion, motility, sensation, and central perception.…”
mentioning
confidence: 99%
“…The 3T-MRN technique is a promising imaging modality and is particularly useful for investigating deeply located DRGs. Studies have reported the usefulness of MRN in assessing DRGs in various neurological disorders [4]. Our study proposes how inflammation and nerve damage progress in SS-SAN.…”
mentioning
confidence: 77%
“…Using qualitative MRN and structural evaluations, the sciatic nerve has shown to be affected in various pathologies, such as hamstring injury due to different causes [5], injection injury after iatrogenic intramuscular infiltrations [6], injury related to hip replacement surgeries [7], perineuriomas [8], Fabry disease [9][10][11], hereditary motor and sensory neuropathies such as Charcot-Marie-Tooth disease (CMTD) [12], or diabetic and other neuropathies [13,14]. These studies conducted primarily visual inspections of the sciatic nerves to detect changes in signal intensities, discontinuities, or lesion loads, often together with evaluations of morphological nerve sizes and volumes [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%